Research on the Application of AI Technology in Digital Exhibition Marketing - Chen, Shu; Yan, Shuwen (Journal of Global Economy, Business and Finance, 2025)
This study focuses on the application of AI technology in digital exhibition marketing. The research methodologies are innovative. First, a literature review method was employed to systematically examine the theoretical foundations of AI technology and exhibition marketing, comprehensively analyzing the latest domestic and international research findings and industry reports. Second, qualitative analysis was used to deeply analyze the AI application practices of companies such as 31 Conference and Miolant 31 Conference, identifying replicable strategies and methods. Key findings are as follows: First, in terms of precision marketing targeting, big data analysis of exhibitor and visitor behavior data was used to construct multi-dimensional customer profiles, enabling personalized recommendations and targeted advertising. For example, 31 Conference's intelligent business recruitment system instantly generates customized exhibition recruitment strategies, while Miolant's AI-powered search function improves the success rate of exhibition invitations. Second, in terms of creative content generation, generative AI was used to rapidly create promotional materials. Third, in terms of optimizing the customer service experience, an intelligent customer service system was deployed to provide 24/7 service, integrating natural language processing technology to enable multilingual support and personalized consultation. The practical value of this study lies in revealing key application paths for AI technology in the exhibition industry, identifying replicable marketing strategies, and helping companies improve marketing efficiency and customer experience, thereby promoting the industry's digital transformation.